Multisensor ground-based measurements of the permafrost thaw subsidence in the Trail Valley Creek, NWT, Canada, 2015-2016 [dataset] - Anders, Katharina; Antonova, Sofia; Beck, Inga; Boike, Julia; Höfle, Bernhard; Langer, Moritz; Marsh, Philip; Marx, Sabrina (PANGAEA - Publishing Network for Geoscientific and Environmental Data, 2018)
Anders, Katharina; Antonova, Sofia; Beck, Inga; Boike, Julia; Höfle, Bernhard; Langer, Moritz; Marsh, Philip; Marx, Sabrina (2018): Multisensor ground-based measurements of the permafrost thaw subsidence in the Trail Valley Creek, NWT, Canada, 2015-2016. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.888566, Supplement to: Marx, Sabrina; Anders, Katharina; Antonova, Sofia; Beck, Inga; Boike, Julia; Marsh, Philip; Langer, Moritz; Höfle, Bernhard (accepted): Terrestrial laser scanning for quantifying small-scale vertical movements of the ground surface in Artic permafrost regions. Earth Surface Dynamics Discussion, 1-31, https://doi.org/10.5194/esurf-2017-49